Prisma Application as A Measuring Instrument of Corporate Obligations to Respect Human Rights - Rehulina Rehulina (Universitas Lampung, 2022)
The corporation’s obligation to human rights is not a moral but a legal obligation. Although in international law, the regulation regarding this corporate obligation is at the level of the Resolution (UN Framework Protect, Respect and Remedy on Business and Human Rights/General Assembly Resolution) and not a convention which is one of the sources of law known in international law. Because many countries follow this provision, it can be categorized as a source of customary international law, which is also a source of international law. However, this paper will not discuss the UN resolution on Human Rights and Business in the sources of international law, but rather how the state implements the resolution and respects or follows the corporation. In September 2014, Indonesia launched the draft National Action Plan (NAP) for Business and Human Rights. Until now, the NAP has not been legalized. However, the Indonesian government has made a policy to ensure that business actors (corporations) respect human rights in running their businesses. In 2021, through the Ministry of Law and Human Rights, the Indonesian government launched an application called PRISMA (Business Risk Assessment and Human Rights). This application aims to help corporations analyze the possibility of violating human rights when they carry out their business activities. This article aims to study and analyze whether the application of PRISMA from a due diligence principal point of view can be an effective tool to measure state duty to protect and corporate compliance with human rights.